Implementasi Model Contextual Teaching and Learning (CTL) pada Pembelajaran IPS untuk Meningkatkan Interaksi Sosial Siswa Kelas VII MTsN 3 Tulungagung - Artha Yoma Nendra Yhakti; Jani Jani (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research is motivated by problems experienced by students, such as continuous problems, the lack of interaction between friends can actually affect the student learning process, especially for class VII. Students are more limited or less active because they lack self-confidence and have difficulty communicating. Therefore, by implementing the contextual teaching and learning model, it is hoped that students can grow their self-confidence so that they can increase social interaction between students and create good learning activities. The research objectives are, to find out the step, supporting and inhibiting factors, impact of implementing the Contextual Teaching And Learning model in social studies learning in increasing the social interaction of class VII students at MTsN 3 Tulungagung. This research uses a qualitative approach, descriptive research type. Descriptive research is presented in the form of words found from observations which are then analyzed, interpreted and conclusions drawn. The population of this study was class VII MTsN 3 Tulungagung and school residents. Data collection techniques use interviews, observation and documentation. The results of the research are drawn to conclusions which show that the implementation of the Contextual Teaching and Learning model can increase social interaction between students, so that students tend to be more active and learning activities can run well.